QR CODE Assisted Mathematics Pocket Book for Grade IV Elementary School. - Mustika, Ayu; Mulyono, Dodik; Satria, Tio Gusti (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2022)
This study aims to determine the level of validity and practicality of the learning media